2019
DOI: 10.1111/ene.14012
|View full text |Cite
|
Sign up to set email alerts
|

Perceived neuropsychological impairment inversely related to self‐reported health and employment in multiple sclerosis

Abstract: Background and purpose Multiple sclerosis (MS) patients frequently report cognitive difficulties which impact daily functioning. The objective was to investigate the relationship between patient‐reported cognitive impairment and depression, demographic and MS‐related variables, and to clarify its impact on self‐reported health measures and employment. Method A large two‐centre survey included the MS Neuropsychological Screening Questionnaire (MSNQ), the two‐question screening tool for depression, vitality, hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 28 publications
2
30
0
Order By: Relevance
“…Most notably, cognitive improvement was not accompanied by a self‐awareness of this positive cognitive change. In keeping with previous research (D'hooghe et al., 2019), we showed that depression influenced how participants perceived their own cognitive abilities, but this does not differ according to cannabis use or abstention.…”
Section: Discussionsupporting
confidence: 92%
“…Most notably, cognitive improvement was not accompanied by a self‐awareness of this positive cognitive change. In keeping with previous research (D'hooghe et al., 2019), we showed that depression influenced how participants perceived their own cognitive abilities, but this does not differ according to cannabis use or abstention.…”
Section: Discussionsupporting
confidence: 92%
“…For a more detailed description of the methods used, we refer to previous publications on this data set. 14,16…”
Section: Methodsmentioning
confidence: 99%
“…For a more detailed description of the methods used, we refer to previous publications on this data set. 14,16 Patients were included if there was a full data set for the screening for depression, EDSS, MSNQ and SDMT scores. One missing value in the MSNQ was imputed by the mean item score.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations